Proiectarea de arhitectură în timp de criză - Adrian Moleavin; Sergiu Cătălin Petrea (Urbanism. Arhitectura. Constructii, 2012)
The phenomenon examined in this paper refers to design principles areas that are affected by environment-related factors and that need to be reinvented. A radical change of the planning process is suggested, because of the crisis that affects the classical notion of housing, rewritten repeatedly during the last century. Analyzing the implications of the phenomenon we immediately notice that the focal point becomes the process (living form) rather than its skin (actual case). Reactive design, as a response to this phenomenon is a process that takes place in the heart of the crisis, therefore is significantly influenced by it. This response critically filters the equation factors and becomes more than a simple taxonomical summation of the main characteristics that archetypal activities present. The aim of this paper is to find plausible answers for the current issues of our built society. The approach implies an investigation of the actual design, focused on various areas, illustrated through a number of case studies. A careful attention is also paid to the impact that new methods of architectural design have upon the housing process, generally considered as a community unifying phenomenon, with all the implications that it entails: socio-cultural, economical, bioclimatic, sustainable.